Measurement of Shear Wave Velocity Using Acoustic Radiation Force Impulse Imaging is not Hampered by Previous Use of Ultrasound Contrast Agents - Cui, X. W.; Pirri, C.; Ignee, A.; De Molo, C.; Hirche, T. O.; Schreiber-Dietrich, D. G.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2014)
Purpose: To assess the inter-observer reproducibility of acoustic radiation force impulse imaging (ARFI) between 2 skilled physicians and to evaluate if ultrasound contrast agents (UCA) affect the measurement of shear wave velocity (SWV) using ARFI.Patients and Methods: 53 patients (29 males, 24 females, 59 ± 15 [22 – 84] years) who underwent contrast enhanced ultrasound (CEUS) examination were included. ARFI was performed on liver segment V by physicians A and B before CEUS, and by physician A within 4 – 6 minutes and 7 – 10 minutes after contrast injection. In a subgroup of 31 patients (15 males, 16 females, 57 ± 18 [22 – 84] years), ARFI was also performed on focal liver lesions (FLL) by physician A before CEUS, and within 4 – 6 minutes and 7 – 10 minutes after contrast injection.Results: The SWV values obtained by physician A and B before CEUS yielded an intra-class correlation coefficient value of 0.913 (95 % CI, 0.849 – 0.950). No significant differences were shown between the SWV values of liver segment V in all 53 patients and of FLL in the subgroup of 31 patients obtained before CEUS and that of within 4 – 6 minutes and 7 – 10 minutes after contrast injection (all P> 0.05).Conclusion: ARFI showed excellent inter-observer reproducibility between 2 skilled physicians. UCA did not affect the measurement of SWV in both liver parenchyma and FLL, at least when performed 4 minutes after the contrast injection. ARFI may become an additional tool in the differential diagnosis of FLL.
Keywords: Leber; Elastografie; Leitlinien; Kontrastmittelultraschall; Reproduzierbarkeit; Scherwelle